2017
DOI: 10.1007/s00702-017-1700-4
|View full text |Cite
|
Sign up to set email alerts
|

Differentiation of atypical Parkinson syndromes

Abstract: In distinction to idiopathic Parkinson's disease (PD), the diagnosis of atypical Parkinson syndromes comprises dementia with Lewy bodies (DLB), multiple system atrophy (MSA), progressive supranuclear palsy (PSP), and corticobasal degeneration (CBD). We set out to write a state-of-the-art guideline as to which investigations and examinations help to differentiate PD vs. atypical Parkinson syndromes in clinical routine.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
20
0
1

Year Published

2017
2017
2022
2022

Publication Types

Select...
6
2
1

Relationship

1
8

Authors

Journals

citations
Cited by 32 publications
(21 citation statements)
references
References 55 publications
0
20
0
1
Order By: Relevance
“…3 Given that DLB and PDD show overlapping clinical and pathological features, [4][5][6] it appears controversial whether they are different diseases or clinical manifestations of the same Lewy bodies disease spectrum. 3 Given that DLB and PDD show overlapping clinical and pathological features, [4][5][6] it appears controversial whether they are different diseases or clinical manifestations of the same Lewy bodies disease spectrum.…”
mentioning
confidence: 99%
“…3 Given that DLB and PDD show overlapping clinical and pathological features, [4][5][6] it appears controversial whether they are different diseases or clinical manifestations of the same Lewy bodies disease spectrum. 3 Given that DLB and PDD show overlapping clinical and pathological features, [4][5][6] it appears controversial whether they are different diseases or clinical manifestations of the same Lewy bodies disease spectrum.…”
mentioning
confidence: 99%
“…Further correlation analysis showed that the CBF of left IFG_Tri was positively correlated with the MMSE score and the CBF of the right cerebellum_crus2 was positively correlated with HAMA and HAMD scores in PPS patients. The association between the hypoperfusion in the cerebellum, thalamus, SMA and the damage in the extrapyramidal system has been described in PPS patients [41]. Thus, more widespread and severe impairment of CBF in PPS might re ect more severity of PPS or later stage of disease.…”
Section: Discussionmentioning
confidence: 94%
“…In addition, CBD can often present with complex cognitive difficulties and neuropsychiatric disturbances 4,5. Symptoms of depression, apathy, or agitation can be subtle and are often overlooked as reactions to receiving a new diagnosis of Parkinsonism 46. Here, we report a case of exacerbated depression with cognitive impairment that was later diagnosed as CBD.…”
Section: Introductionmentioning
confidence: 93%